Investigative competence as a pedagogical tool in the teaching of law - Palacios Hernández, Alex Antonio; Córdoba Robledo, Carlos Andrés; Palacios Hernández, Alex Antonio; Córdoba Robledo, Carlos Andrés; Palacios Hernández, Alex Antonio; Córdoba Robledo, Carlos Andrés (Corporación Universitaria Americana, 2020)
The discussion around the training and evaluation by competencies day by day becomes more relevant in the national academic panorama, today it ceased to be an exclusive concern of pedagogues to become a vital matter of training in the different academic programs in education higher education, particularly in the teaching of area law in which it is non-extendable to adopt measures that facilitate and contribute to the training of professionals who can respond to the paradigms of globalization, free trade and post-conflict. Thus generating the great challenge for the faculties and the responsibility for teachers to improve the teaching - learning process within the law faculties, being of great benefit for this purpose, the development of investigative competence in law students, with the purpose, that this pedagogical tool that facilitates and optimizes the quality of the training that is being imparted.